Imaging findings of primary epithelioid sarcoma of adrenal gland: a case report and literature review - Yin, Hongyu; Zhang, Yi; Wu, Linyun; Zhang, Ji (Frontiers in Oncology, 2023)
Epithelioid sarcoma (ES) is a rare soft tissue malignant tumor with an uncertain histogenetic origin. It usually arises in soft tissues of the extremities, while ES in adrenal gland is extremely rare. There is no special clinical manifestation in the early stage, so it may be misdiagnosed and delay the treatment. We reported a 69-year-old male with an adrenal ES. The tumor was completely resected and there is no metastasis and recurrence during the follow-up 10 months. We summarize the radiological findings of primary epithelioid sarcoma of adrenal gland, which may be useful to promote disease awareness and helpful to distinguish among other lesions.